Increasing Teachers' Ability in Applying Outing Class-Based Contextual Learning Models Through Workshops for Teachers of SD Negeri Bendo Kapanewon Samigaluh Teachers for the 2022/2023 Academic Year - Saminem, Fransisca (IJCER (International Journal of Chemistry Education Research), 2024)
The aim of this research is to improve teachers' ability to use an outing class-based contextual learning model and to improve the ability of school principals to manage workshops using an outing class-based contextual learning model. This type of research is school action research carried out in two cycles. Each cycle is carried out in two meetings, with a time allocation of 4x35 minutes for each meeting. Each meeting has four main activities, namely 1) planning, 2) implementation, 3) observation, and 4) reflection. In cycle I the researcher presented material on the nature of learning models, the preparation of learning steps. Cycle II carried out the preparation of learning implementation plans and teaching practices. There were 8 participants involved, consisting of 6 class teachers and 2 subject teachers. The research results showed that in cycle I, the participants' ability to use the outing class-based contextual learning model increased. At the 1st meeting it reached 72.32%; the 2nd meeting reached 83.93%. Meanwhile, the results of cycle II for the 1st meeting reached 88.84%, the results for the 2nd meeting reached 94.20%. The results of the principal's ability to manage the workshop were obtained in the first cycle for the 1st meeting reaching 84.92%, for the 2nd meeting reaching 86.22%. The results in cycle II of the 1st meeting reached 87.40%; and the 2nd meeting reached 90.28%. So it can be said that the ability of teachers to use the contextual learning model based on outing classes and the ability of school principals to manage workshops using the contextual learning model based on outing classes have increased significantly.